Factors Associated with Turnover Intentions of Nurses Working in Japanese Hospitals Admitting COVID-19 Patients - Yoshiko Kitamura; Hisao Nakai (Nursing Reports, 2023)
Three years after the outbreak of the coronavirus disease (COVID-19) pandemic, turnover among frontline nurses has increased. The participants of this study were nurses at two general hospitals in Ishikawa, Japan, receiving COVID-19 patients. An original self-report questionnaire was created based on previous research. The questionnaire was distributed to 400 nurses, and responses were received from 227 nurses (response rate: 56.8%). The factors influencing turnover intention at the facilities were having less time to relax (odds ratio [OR]: 2.88, 95% confidence interval [CI]: 1.12–7.41) and wanting to receive counseling (OR: 5.21, 95% CI: 1.30–20.91). As a strategy to prevent turnover, nurse managers should provide opportunities for nurses to receive counseling during normal working hours and pay particular attention to changes in nurses’ daily lives, such as changes in the time available for relaxation.